The safety centre – product, education, location. (1st March 2011) - Smith, S J; Phillips, K
Abstract : Introduction: Detroit, like many impoverished cities, does not have stores where families can buy the products, for example, car seats, helmets, smoke alarms, etc, to keep their children safe. When the paediatrician recommends products to protect the child, the family must go to the suburbs to acquire these necessary items. Many of the families in Detroit do not have cars and must obtain a ride from a friend, take the bus or taxi, which is expensive. Implementation: To remove those barriers, on August 4, 2008, Children's Hospital of Michigan opened The Safety Center to improve the safety of all children by providing education (for staff and families) and safety items at an affordable cost in the communities where the children live. The Safety Center is a permanent location in the hospital, has a mobile kiosk that can be taken to any location and is accessible via the web. Additional Safety Centers are being considered for placement around Southeast Michigan. Education is given to the customer on how to use every item sold. Families, Physicians and hospital staff use the Center as a resource to purchase products and learn the latest in safety products and education. Families can get a safety assessment done and receive a plan of care to keep their family safe. Safety Center staff is consulted to hospital rooms, offsite satellites and even other hospitals to help families with safety issues. Since opening, the Center has helped 2589 families purchase safety products to keep their children safe.